Affectivity as a tool in the adhesion to guidelines on education in oral health in the Family Health Program - Ferreira dos Santos, Suely; Souza Leite Campinas, Lúcia de Lourdes; Alves Lopes Sartori, Jaqueline (O Mundo da Saúde, 2010)
Education in Oral Health has a direct relation to the reasons that make people not to modify their oral hygiene habits or to have difficulty for incorporating them in its daily life even as this knowledge is easily transmitted by the oral health team but not always incorporated by patients. The work aimed at studying affectivity as a strategy to be used in education in oral health, in order to cause changes that surpass negative or passive attitudes. The methodology was an integrative bibliographical search. We believe that if our objective as professionals of odontology is promoting better health conditions and reduce the high rate of caries and dental losses, education in health must be significant to the patient. We always hear that education and health have to walk together, but how to really work for this to happen? The description of surveys epidemiologists carried through in our country brings pictures of contrasts and few improvements of quality on some aspects of oral health. The indices of research make us think that the oral condition in the population is still poor and that changes are slow. The change will have to begin in the professional training of surgeons-dentists, and assistants and technicians in oral health (CD, ASB and TSB, respectively), that follows a model where the main focus are the development of the hand abilities of professionals and clinical procedures. To modify this situation we need to act in a simpler and productive way. Instructions on hygiene, feeding and habits may be transmitted by all the members of oral health team using technical knowledge allied to a new tool: “Communication with Affectivity”. In any communicative act, we must always search the understanding of the universe of individuals, which has their own values, motivations, and experiences. We will not change the sad situation of oral health in Brazil if we continue the old techniques without considering affectivity as a strategy.